Fans For Greenhouses - D. E. Buffington; R. A. Bucklin; R. W. Henley; D. B. McConnell (EDIS)
Fans are used in processing applications involved with drying, ventilating, heating, cooling, aspirating, elevating, and conveying. Processing and other agricultural activities requiring fans are greatly increasing. Costs are becoming more and more important; therefore, it is necessary that a person be able to select and apply the best fan for any installation, taking economic factors into consideration. This article introduces some important fan properties that you should consider when select a fan, such as types, noise levels, volume flow rates and characteristic curves. Inspection and maintenance guidelines are provided for maintaining the functionality of the fans and minimizing breakdowns.